TERAPI PEMAAFAN TERHADAP KESEPIAN LANSIA SAAT PANDEMI COVID-19 - Jessica Christina Widhigdo (Universitas Mercu Buana Jakarta, 2023)
COVID-19 pandemic impacts the mobility of adults, especially the elderly. The elderly have experienced a significant impact due to the COVID-19 pandemic. One of the impacts experienced by the elderly is isolation from the surrounding environment. The beliefs or expectations of the elderly on the behavior of children to pay attention and care for themselves in old age can affect the well-being of the elderly. When expectations do not match reality, the elderly will feel disappointed, angry, stressed, and feel lonely in their lives. The purpose of this study was to determine the impact of forgiveness therapy on the loneliness score of the elderly. This study involved three participants aged 70-80 years. Data analysis in this study used the paired sample t-test. The instruments used are the UCLA loneliness and Heartland Forgiveness Scale (HFS). The results showed that there was a difference in loneliness scores in the elderly before and after following forgiveness therapy (sig 0.008 <0.05).